Tuesday

September 23, 2014

September 23, 2014

Posted by **Sara** on Thursday, July 19, 2007 at 9:28pm.

S = a/(1-r)

Multiply both sides by 1-r

S*(1-r) = [(1-r)*a]/(1-r)

Simplify

S*(1-r) = a

Multiply terms on the left.

S - S*r = a

Subtract S from both sides.

S-S*r - S = a - S

Simplify

-S*r = a - S

Multiply both sides by -1

S*r = -a+S

Divide both sides by S

S*r/S = (-a + S)/S

r = (S-a)/S

Check my work carefully.

**Answer this Question**

**Related Questions**

Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...

Maths - you have to solve the following by finding the value of x and y. can u ...

Pre-Algebra - inequality 0.75x>3 Multiply both sides of the inequality by 4/3...

someone help - my post is still on this page as algebra, could someone elaborate...

Solving Equations with Rational Expressions - Can someone please show me how to ...

math, algebra - Problem: A formula for a football player's rushing average r ...

Algebra 2 - -2/3x + 3<11 how do i solve this equation Subtract 3 from both ...

Algebra - Solve each literal equations for the indicated variable D = C - s/n ( ...

math - how do you solve 9x=6 9x=6 Divide both side by 9. (Remember you can add, ...

math 117 - 5/(x+6)+ 2/(x^2+7x+6)= 3/(x+1) Rewrite x^2 +7x +1 as (x+6)(x+1) ...